Effectiveness of Modified Holmich Protocol on strength, functional performance and injury prevention of groin injuries among U‑19 female footballers - Riya Gupta; Aditi Singh; Anu Bansal (Bulletin of Faculty of Physical Therapy)
Abstract Background Adductor-related groin pain syndrome is the most common problem for athletes in many sports which often significantly reduces athletic performance and activity. Objective This study aimed to investigate the effectiveness of the Modified Holmich protocol on hip adductor strength, functional performance, and injury prevention in U-19 female footballers with groin discomfort. Methods An experimental study was conducted with a total of 34 U-19 female footballers from Olympus Sports Club in Noida. Participants were randomly assigned to either the experimental group (n = 17) or the conventional group (n = 17). The experimental group followed the Modified Holmich protocol, while the conventional group followed a general strengthening protocol. Baseline measurements of hip adductor strength, functional performance (measured using the Edgreen Side Hop Test), and groin-related issues (assessed using the HAGOS questionnaire) were obtained. Results The Modified Holmich Protocol group showed significant strength gains (Left: 18.3 ± 2.3 to 20.4 ± 2.2; Right: 19.6 ± 2.4 to 21.1 ± 2.4; p < 0.001) and functional improvement (ESST: 10.7 ± 1.9 to 12.1 ± 1.6, p < 0.001), outperforming conventional training (ESST post: 12.1 ± 1.6 vs 10.6 ± 1.5, p = 0.01). HAGOS subscales demonstrated clinically meaningful improvements (Pain: 63.4 ± 4.2 to 69.7 ± 4.1; Symptoms: 63.8 ± 4.7 to 68.9 ± 4.0; ADL: 62.7 ± 5.6 to 70.0 ± 4.0; Sports: 67.8 ± 4.5 to 72.6 ± 3.1; all p < 0.001), confirming the protocol's effectiveness for enhancing both physical capacity and patient-reported outcomes in female footballers. Conclusion The findings suggest that the Modified Holmich protocol is effective in improving hip adductor strength, functional performance, and reducing groin-related issues in U-19 female footballers with groin discomfort. Trial registration Clinical Trials Registry-India (ICMR-NIMS) registry no. CTRI/2023/02/049371.